Effectiveness of Financial Investment Risk Management of Dana Haji Indonesia - Alif Ilman Mansyur (Jurnal Ilmiah Ekonomi Islam, 2021)
Instructions This study aims to see how the financial condition of Hajj Funds in Indonesia and has the authority to manage Hajj financial investments in Indonesia. The research method used a descriptive qualitative approach, namely by understanding the various concepts found in the research process, research techniques using content analysis and library research. in this study using secondary data sources and types obtained from research results, articles and reference books that discuss topics related to the research theme. The results show that first, the development of financial conditions for Hajj investment in Indonesia in the May 2020 period amounted to Rp. 135 trillion and the ranking of funds seen from the source, namely the initial deposit of Rp. 132 trillion and the people's endowment fund of Rp. 3.4 T, then viewed in terms of the value of assets / funds under management and the value of the benefits of the BPKH that are produced at a value of Rp. 125 trillion in 2019. Second, which has financial management risk for Indonesian hajj funds who see the risks that occur, the main control that must ensure that the main hajj fund financial investment risks can be managed effectively, Identify the Team / Individual responsible for ensuring the main control operate as required, Identify the Team / Individual responsible for ensuring the main controls operate as required.